Tectonic position of the Ukrainian shield - Goryainov, Sergey (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Statement of the general problem. The analysis of the geological structure of Europe indicates a wide development of Laramian (post-Cretaceous - pre-Cenozoic) deformations in non-Alpine regions. They are traced by the regional angular unconformity between the folded Mesozoic and non-folded Cenozoic from the Caspian Sea to Great Britain. The area of development of the Laramie folding of Europe also covers the Ukrainian shield.An unsolved part of the overall problem. The Ukrainian crystalline shield is described as "uplift of the crystalline foundation of the East European platform", where Precambrian rocks come to the surface. But the same rocks can also be traced far beyond its borders. The question arises - what structural position does the Ukrainian shield occupy in the structure of the Laramie folded region?Analysis of recent research and publications. On the geological maps of the pre-Cenozoic formations of Ukraine, the northern border of the Laramie folded region can be traced along the Chernihiv-Lysychansk line. Mesozoic folds and an angular unconformity in the Cenozoic basement disappear further north. To the south, the Laramie deformations intensify, but unevenly.The purpose of the article is identification of modern structural position of Ukrainian crystalline shield.Research materials and methods. Were involved more than 120 geological maps of Ukrainian regions and author's digital geological model of East Ukraine.Presentation of the main research material. A band of Mesozoic folds and NW vergence thrusts tens to hundreds of kilometers long is developed immediately south of the border of the folded region. The amplitude of the folds is 1.5–2 km. The band of development of these folds and thrusts with a width of about 100 km limits the Ukrainian shield from the northeast.To the south of the Ukrainian Shield, on the shelves of the Black and Azov Seas and in Northern Crimea, a sub-latitude band of Laramie thrusts and folds with a width of 150–200 kilometers has been established. Amplitudes of thrust folds reach 1–2 km, amplitudes of separate thrusts reach 8–10 km. This band of folds and thrusts limits the southern slope of the Ukrainian shield from the south. These Laramie folds and thrusts are overlain by Cenozoic sediments.To the south, in the Mountainous Crimea, the deformations are still intensifying. Folds and thrusts are replaced by wide and extended mélange zones of northwestern vergence.The Ukrainian shield is bypassed by the development of folds and thrusts from the northeast, east, and south. On the slopes of the Ukrainian shield, Mesozoic fold deformations subside, and the Mesozoic there lies gently sloping and monoclinally. Such poorly deformed blocks within folded regions are called middle massifs. This middle massif of the Laramie fold region within Ukraine has an anteclise structure. In the core of the anteclise, Precambrian metamorphic and igneous rocks emerge from under the sedimentary cover. The western wing of the anteclise is overlain by younger thrusts of the Carpathian folded structure of Attic (post-Miocene) age.Scientific novelty. In the modern geological structure, the Ukrainian shield is the core of the anteclise of the middle massif in the Laramie folded region.Conclusions. As a tectonic uplift, shield was formed in the Paleocene. In the Late Cretaceous, it was still buried under shelf carbonate deposits. Erosion of this uplift formed the Cenozoic deposits of Ukraine with a specific mineragenic specialization. Taking into account the Laramian folding allows us to reconcile the diverse geological phenomena of the region into a single system without contradictions.